Numerical simulation of vortex-induced drag of elastic swimmer models - Engels, T.; Kolomenskiy, D.; Schneider, K.; Sesterhenn, J. (Theoretical and Applied Mechanics Letters, 2019)
We present numerical simulations of simplified models for swimming organisms or robots, using chordwise flexible elastic plates. We focus on the tip vortices originating from three-dimensional effects due to the finite span of the plate. These effects play an important role when predicting the swimmer`s cruising velocity, since they contribute significantly to the drag force. First we simulate swimmers with rectangular plates of different aspect ratios and compare the results with a recent experimental study. Then we consider plates with expanding and contracting shapes. We find the cruising velocity of the contracting swimmer to be higher than the rectangular one, which in turn is higher than the expanding one. We provide some evidence that this result is due to the tip vortices interacting differently with the swimmer.